2018
DOI: 10.1038/s41598-018-35297-4
|View full text |Cite
|
Sign up to set email alerts
|

Quenched Stochastic Optical Reconstruction Microscopy (qSTORM) with Graphene Oxide

Abstract: Quenched Stochastic Optical Reconstruction Microscopy (qSTORM) was demonstrated with graphene oxide sheets, peptides and bacteria; a method of contrast enhancement with super-resolution fluorescence microscopy. Individual sheets of graphene oxide (GO) were imaged with a resolution of 16 nm using the quenching of fluorescence emission by GO via its large Resonant Energy Transfer (RET) efficiency. The method was then extended to image self-assembled peptide aggregates (resolution 19 nm) and live bacterial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…This PLLGO coating improves the signal-to-noise ratio (i.e., the contrast) for fluorescence imaging by a factor of 100. 41…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This PLLGO coating improves the signal-to-noise ratio (i.e., the contrast) for fluorescence imaging by a factor of 100. 41…”
Section: Methodsmentioning
confidence: 99%
“…In addition, confocal and super-resolution (dSTORM) microscopies were used without the washing step with the immunostaining methods by incubating both primary (1:8000) and secondary (1:10 000) antibodies at a lower concentration with the bacteria due to the benefits of using PLLGO-coated slides, i.e., the PLLGO coating removed the background due to nonspecifically bound fluorophores and provided a 100 factor of improvement in contrast. 1 The polylysine coating has a negligible effect on the proliferation of the bacteria over a period of 3 h (the time for a complete capsule to form, Supporting Information (SI 5)).…”
Section: Methodsmentioning
confidence: 99%
“…The fluorescence from the graphene is initially unexpected. All fluorophores less than 10 nm from graphene or GO are expected to quench their fluorescence due to resonant energy transfer (RET) [87][88][89], an effect that has been used for contrast enhancement in STORM [66]. This RET is suppressed at edges and other defects in graphene [90]; however, the control experiment in which the dye conjugation procedure was repeated on CVD G-SO 3…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it can be used to cooperate with quenched stochastic optical reconstruction microscopy (qSTORM) to achieve the super-resolution imaging effect of self-assembled peptide fibrils and Escherichia coli. In 2018, Li et al experimentally demonstrated that GO coating with qSTORM could increase the imaging resolution and contrast [ 102 ] when imaging the peptides and bacteria via the strong quenching effect. Due to the same hexagonal lattice and similar electronic properties for both graphene and GO, the quenching effect is advisable with GO.…”
Section: Alternative Imaging Devices Integrated With Graphene Oxidementioning
confidence: 99%
“…( b ) Reconstructed STORM image of peptide fibers. Reprinted with permission from [ 102 ]. Copyright 2018 Springer Nature.…”
Section: Figurementioning
confidence: 99%